Intoxicação experimental por Ateleia glazioviana em ovinos: patogênese e bases morfológicas da falha reprodutiva, da insuficiência cardíaca e dos distúrbios neurológicos - Raffi, Margarida Buss (2004)
This experiment was undertaken to study the following aspects of the A. glazioviana poisoning in sheep: (1) abortifacient properties of the plant and the pathogenesis of the abortions and reproductive failure associated with the toxicosis and (2) the morphology and pathogenesis of cardiac and brain lesions. In the first part of the experiment, 17 pregnant ewes were orally fed variable amounts of either green or dried leaves of A. glazioviana fractioned in 1-24 daily doses. All 17 ewes manifested some form of reproductive failure. Nine (52.9%) aborted their fetuses at 4-36 days after starting being fed the leaves of the plant; one had a stillbirth and in another one intrauterine fetal death was diagnosed. The other six ewes delivered 8 weak lambs seven of which died from few minutes to 48 hours after birth. Gross and histopathological changes observed in lambs, stillborn, and in aborted fetuses were rather similar to those found in the spontaneous poisoning by A. glazioviana in ruminants. It is concluded that abortions caused by A. glazioviana are due to transplacental induced fetal lesions consisting of toxic cardiomyopathy and spongy degeneration of the white matter of the brain. For the second part of the experiment 15 mature sheep were fed varying daily amounts of the fresh green leaves of A. glazioviana for different periods of time (1-24 days). Clinical signs observed in poisoned sheep included depression, anorexia, general weakness, staggering gait and prolonged recumbency. One sheep had signs of congestive heart failure. Necropsy findings included subcutaneous and cavitary edema in two sheep and nutmeg liver in one. Histopathological findings included degeneration, necrosis and interstitial fibrosis in the myocardium of 4 sheep and spongy degeneration of cerebral white matter (status spongiosus) in 10 sheep. The ultrastructure of the brain lesion was morphological consistent with those found in diseases grouped as spongiform myelinopathies in which vacuolation of myelin occur in absence of significant myelin break down or phagocytosis